2020
DOI: 10.1111/rec.13194
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of soil phosphorus on former bauxite mines through tropical forest restoration

Abstract: Soil phosphorus (P) is a major driver of forest development and a critically limited nutrient in tropical soils, especially when topsoil is removed by mining. This nutrient can be present in soils in the form of different fractions, which have direct consequences for P availability to plants and, consequently, for restoration success. Therefore, understanding how the stocks of different soil P fractions change over the restoration process can be essential for guiding restoration interventions, monitoring, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…So its fast accumulation in ecosystems undergoing restoration is critical for their ecological sustainability. An earlier study conducted in the same region showed that restoration interventions successfully recovered different P fractions (Bizuti et al., 2020), which may have been key to enhance primary productivity and litter production, given the naturally low levels of P in tropical soils, especially in mined substrates (Shrestha & Lal, 2011; Vitousek et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So its fast accumulation in ecosystems undergoing restoration is critical for their ecological sustainability. An earlier study conducted in the same region showed that restoration interventions successfully recovered different P fractions (Bizuti et al., 2020), which may have been key to enhance primary productivity and litter production, given the naturally low levels of P in tropical soils, especially in mined substrates (Shrestha & Lal, 2011; Vitousek et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mining is one of the most profitable activities in the world, but it is also one of the most damaging on the environment. Often located in high‐diversity and endangered ecosystems, like the Jarrah Forests in Australia (Koch & Hobbs, 2007), the Atlantic Forest of Brazil (Bizuti et al., 2020) or the Congo Basin Forest in Africa (Edwards et al., 2014), mining activities jeopardize biodiversity and ecosystem functioning through the removal of vegetation and topsoil. As a consequence, mining is often associated with a strong reduction of organic matter and nutrient stocks in the soil (Tripathi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate phosphorus deficiency in tropical soils, especially in areas under recovery, it is common to apply high doses of phosphate fertilizers aiming for a more efficient growth of vegetation, which often does not occur due to the dynamics of adsorption. Therefore, studies involving soil P adsorption and availability are important for the success of soil fertilization programs, especially in forest recovery projects (Bizuti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fertiliser is prescribed for ecological restoration where there is insufficient quantity or availability of soil nutrients (Whisenant 1999). Consequently, the application of fertiliser is considered necessary, to replace nutrients lost in vegetation and soils, and best practice, to kickstart restoration of native plants and ecosystems after surface mining in Brazil, Canada, and Australia (Bizuti et al 2020;Pinno et al 2012;Tibbett 2010). Yet, in other restoration contexts the removal of soil nutrients is often required to kickstart restoration (e.g.…”
Section: Introductionmentioning
confidence: 99%